Family involvement and participation in schools in Portugal: The difficulty in sharing responsibilities - Gonçalves, E. (Parental involvement across European education systems: Critical perspectives, 2020)
In Portugal, the school–family relationship should be an important research area, because families’ roles and choices in education increased after the legislative changes implemented since the 1980s. Schools have to cooperate with their local communities, teachers must accept the right of families to participate in decision-making processes, and families are encouraged to accept new roles as partners and stakeholders. Results from a multiple-case study of six schools – characterised by different socioeconomic contexts and levels of academic performance and located in three different municipalities in Portugal – reveal that even though families have more opportunities to participate, many still have not adopted their new roles. Also, results demonstrate that the principals’ interpretation of legislation affects the outcomes between schools where families are real stakeholders and/or partners and schools where having family representatives in the management structures is a mere bureaucratic-administrative drill. Most families do not play a formal role in schools and do not make use of their new rights, either because they do not know about the existence of their representatives in General and Class Councils, or they choose to not engage, preferring to talk directly to teachers to solve problems or give suggestions for improvements.